Insights from Fumarole Gas Geochemistry on the Recent Volcanic Unrest of Pico do Fogo, Cape Verde - Melián, Gladys V.; Hernández, Pedro A.; Pérez, Nemesio M.; Asensio-Ramos, María; Padrón, Eleazar; Alonso, Mar; Padilla, Germán D.; Barrancos, José; Sortino, Francesco; Sumino, Hirochicka; Rodríguez, Fátima; Amonte, Cecilia; et al. (Frontiers in Earth Science, 2021)
We report the results of the geochemical monitoring of the fumarolic discharges at the Pico do Fogo volcano in Cape Verde from 2007 to 2016. During this period Pico do Fogo experienced a volcanic eruption (November 23, 2014) that lasted 77 days, from a new vent ~2.5 km from the fumaroles. Two fumaroles were sampled, a low (F1~100ºC) and a medium (F2~300ºC) temperature. The variations observed in the δ18O and δ2H in F1 and F2 suggest different fluid source contributions and/or fractionation processes. Although no significant changes were observed in the outlet fumarole temperatures, two clear increases were observed in the vapor fraction of fumarolic discharges during the periods November 2008-2010 and 2013-2014. Also, two sharp peaks were observed in CO2/CH4 ratios at both fumaroles, in November 2008 and November 2013. This confirms that gases with a strong magmatic component rose towards the surface within the Pico do Fogo system during 2008 and 2013. Further, F2 showed two CO2/Stotal peaks, the first in late 2010 and the second after eruption onset, suggesting the occurrence of magmatic pulses into the volcanic system. Time series of He/CO2, H2/CO2 and CO/CO2 ratios are low in 2008-2009, and high in 2013-2014 period, supporting the hypothesis of fluid input from a deeper magmatic source. Regarding to the isotopic composition, increases in air-corrected 3He/4He ratios are observed in both fumaroles. The suite of geochemical species analyzed have considerably different reactivities, hence these integrated geochemical time-series can be used to detect the timing of magmatic arrivals to the base of the system, and importantly, indicate the typical time lags between gas release periods at depth and their arrival at the surface. The high 3He/4He ratios in both fumaroles in the range observed for mid-ocean ridge basalts, indicating that He is predominantly of upper mantle origin. This work supports that monitoring of the chemical and isotopic composition of the fumaroles of the Pico do Fogo volcano is a very important tool to understand the processes that take place in the magmatic-hydrothermal system and to be able to predict future episodes of volcanic unrest and to mitigate volcanic risk.